El indigenismo peruano (1920-1930) desde dos direcciones ideológicas: el arte y la literatura - Villanueva Ccahuana, Philarine Stefany (2019)
It analyses the indigenism (or indigenism) that arises in the years 1920 to 1930 in the field of literature and art. Review the theoretical proposals formulated by Luis Alberto Sánchez and José Carlos Mariátegui in the field of literature; and José Sabogal in art. The study is based on the analysis and interpretation of discourses and (re) examines the indigenism from the ideological level of two disciplines whose particular ways of conceiving indigenism does not prevent the identification of common approaches.